Evaluator education through an LGBTQ+ lens: Interrogating power and privilege in the classroom. Issue 175 (21st October 2022) - Wright, Morgan M.; LaVelle, John M.
Abstract: The long‐term sustainability and stability of the evaluation profession is dependent on superior, evaluation‐specific education programs designed to help increase the quality, numbers, visibility, and collective impact of evaluation theory and practice in society. Recent studies illustrate the breadth of colleges and universities in the United States that are offering certificates, master's degrees, and doctoral degrees with a specialization in evaluation. Less attention has been paid, however, to the ways higher education institutions prepare would‐be evaluators to recognize the limits of their expertise and to work with individuals and communities that may not share their expertise or background. The importance of this awareness is compounded by the ethical challenges associated with facilitating evaluative work with diverse, historically marginalized groups such as LGBTQ+ communities, which may have their own fraught histories with evaluation. This chapter will discuss LGBTQ+ perspectives that educators should include in their evaluation curricula to help inform high‐quality, ethical practice, and conclude with a dialogue between the authors about the process of writing the chapter, their concerns, and their hopes for the future.